Ultrasonographic evaluation of mandibular elevator muscles to assess effects of attrition-type tooth wear on masticatory function - Fatma Avcı; Gözde Özcan; Duygu Göller Bulut (Cumhuriyet University, 2018)
Objectives: Occlusal alterations may result in changes in the functional performance of masticatory muscles. This study was planned to evaluate mandibular elevator muscles of patients with dental attrition by using ultrasonography (USG). Methods: 30 physiologically dental attrition subjects, aged 35-65 years, were clinically examined by tooth wear index (TWI). Patient group (TWI scores of 2-4) and age-matched controls (TWI scores of 0-1) underwent ultrasonographic analysis to assess the thickness of anterior temporalis, superficial masseter muscles, bilaterally, during clench and rest positions. Results: The mean thickness of masseter and temporal muscles for rest and clench positions and the ratio between thickness of clench and rest position (C/R) were evaluated. Muscle thickness had a higher mean value in the tooth wear group. However, the only significant differences were in the C/R ratio for left side of masseter (p=0.04) and temporal muscles (p=0.03). Although, there was a negative correlation between TWI scores and the muscle C/R ratio for the tooth wear group. A significant positive correlation was found between age and TWI in both groups. Conclusion: The contraction capacity of the chewing muscles and the attrition mutually interact. This study showed an associate on between the severity of occlusal tooth wear and the C/R of chewing muscles. Although dental attrition can occur due to increased jaw muscle activation, and it can also cause a reduction in the contraction capacity of mandibular elevator muscles.